2021
DOI: 10.1002/mgg3.1685
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous GDF2 nonsense mutations result in a loss of circulating BMP9 and BMP10 and are associated with either PAH or an “HHT‐like” syndrome in children

Abstract: Background: Disrupted endothelial BMP9/10 signaling may contribute to the pathophysiology of both hereditary hemorrhagic telangiectasia (HHT) and pulmonary arterial hypertension (PAH), yet loss of circulating BMP9 has not been confirmed in individuals with ultra-rare homozygous GDF2 (BMP9 gene) nonsense mutations. We studied two pediatric patients homozygous for GDF2 (BMP9 gene) nonsense mutations: one with PAH (c.[76C>T];[76C>T] or p.[Gln26Ter];[Gln26Ter] and a new individual with pulmonary arteriovenous malf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 47 publications
3
35
1
Order By: Relevance
“…Previous studies have measured BMP9 and pBMP10 plasma levels along with the serum-derived endothelial BMP activity in patients with homozygous nonsense GDF2 mutations, PAH patient and a patient with "HHT-like" phenotype. They confirmed that it results in reduced plasma BMP9 and pBMP10 levels, even in asymptomatic heterozygous parents [33]. Furthermore, the variant specifically detected in patient 1 in this study has been previously described in heterozygosis by Hodson et al [32] in a female patient diagnosed at 46 years with PAH.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have measured BMP9 and pBMP10 plasma levels along with the serum-derived endothelial BMP activity in patients with homozygous nonsense GDF2 mutations, PAH patient and a patient with "HHT-like" phenotype. They confirmed that it results in reduced plasma BMP9 and pBMP10 levels, even in asymptomatic heterozygous parents [33]. Furthermore, the variant specifically detected in patient 1 in this study has been previously described in heterozygosis by Hodson et al [32] in a female patient diagnosed at 46 years with PAH.…”
Section: Discussionsupporting
confidence: 89%
“…However, three other children under the age of ten years with homozygous truncating variants showed no evidence of PAH (confirmed by right heart catheterization in one) (49,50), suggesting that homozygosity does not necessarily lead to early age of onset or more severe disease, and thus GDF2 variants may act as a dominant gene in PAH susceptibility. There is also an emerging picture of overlap with HHT-like phenotypes, notably pulmonary arteriovenous malformations, that is beyond the scope of this manuscript (49)(50)(51).…”
Section: The Identification Of Homozygous Gdf2mentioning
confidence: 97%
“…Along with the genetic lesion in a predisposed (heterozygous) background, an environmental disturbance that causes increased angiogenesis and/or inflammation in the context of altered shear stress and blood flow patterns is necessary to generate an AVM [ 187 ]. Mutations in ENG, ALK1 , SMAD4 and GDF2 (Bmp9) are linked to human diseases involving AVM formation [ 9 , 11 , 27 , 188 , 189 ]. Such diseases include Hereditary Hemorrhagic Telangiectasia (HHT), where the resulting AVMs are prone to vessel wall fragility; this fragility leads to hemorrhage, which can be fatal if located in the brain, liver, or lungs [ 190 ].…”
Section: Chapter 22: Bmp Signaling In Vascular Patterningmentioning
confidence: 99%